Langgam Bayang, Sabda Kelir: Peran dan Kontribusi Ki Narto Sabdo dalam Pelestarian Wayang Kulit di Semarang (1945-1985) (Lembaga Pengembangan Kinerja Dosen, 2025)
Ki Narto Sabdo is an important figure in Javanese culture, especially in Semarang. During the period from 1945 to 1985, through innovations in the art of wayang kulit puppetry, he successfully preserved, developed, and revitalized the wayang tradition amidst the modernization and socio-political dynamics of Indonesia. As a master puppeteer and innovator in performance styles, Ki Narto Sabdo not only created hundreds of new gending and lakon rich in Javanese moral, spiritual, and philosophical values, but also built a cultural preservation ecosystem. He did this through the establishment of art studios, mentoring young puppeteers, and cross-style collaborations that resulted in the distinctive Semarang wayang. In the context of significant socio-cultural changes in Indonesia from post-independence to the New Order, his contributions not only influenced the continuity of performing arts. Ki Narto Sabdo also played an important role in strengthening wayang kulit as a tool for character education, uniting communities, and driving the local cultural economy. By analyzing in depth the role and influence of Ki Narto Sabdo on the art community, cultural institutions, and the regeneration of wayang kulit artists in Semarang, this research aims to provide a more specific and contextual understanding of cultural heritage preservation strategies.